LIF diagnostics of hydroxyl radical in a methanol containing atmospheric-pressure plasma jet - 钱沐杨 刘三秋 裴学凯 卢新培 张家良 王德真 (Chinese physics B, 2016)
In this paper, a pulsed-dc CH3OH/Ar plasma jet generated at atmospheric pressure is studied by laser-induced fluorescence（LIF） and optical emission spectroscopy（OES）. A gas–liquid bubbler system is proposed to introduce the methanol vapor into the argon gas, and the CH3OH/Ar volume ratio is kept constant at about 0.1%. Discharge occurs in a 6-mm needle-to-ring gap in an atmospheric-pressure CH3OH/Ar mixture. The space-resolved distributions of OH LIF inside and outside the nozzle exhibit distinctly different behaviors. And, different production mechanisms of OH radicals in the needle-to-ring discharge gap and afterglow of plasma jet are discussed. Besides, the optical emission lines of carbonaceous species, such as CH, CN, and C2 radicals, are identified in the CH3OH/Ar plasma jet. Finally, the influences of operating parameters（applied voltage magnitude, pulse frequency, pulsewidth） on the OH radical density are also presented and analyzed.